The Presence of Cataract Does Not Influence Assessment of The Pupillary Light Reflex Using Automated Pupillometry - Sonja Stutzman; DaiWai Olson; Aardhra Venkatachalam; Arianna Barnes; Folefac Atem (San Beda University, 2021)
Background: Advanced Pupillary Light Reflex (PLR) assessment with an automated infrared pupillometer (AIP) is becoming standard. Although cataract prevalence and risk for neurologic illness both increase with age there is no literature on the influence of cataract when assessing PLR using AIP. Objective: Our aim is to explore the effect of cataract on pupillary response to light. Methods and Materials: Mixed model analyses were performed by enrolling 3,650 patients with PLR readings from AIP.  The Neurological Pupil Index (NPi), and each component of the PLR was examined separately. Results: 3,207 patients did not have cataract, 59 had unilateral, and 271 bilateral cataract. Generalized linear mixed effect model of 87,290 right eye, and 76,587 left eye AIP measurements found no effect of cataract on any PLR measures: NPi (p=0.221 and p=0.655); latency (p=0.483 and p=0.865); initial pupil size (p=0.661 and 0.712); minimum pupil size (p=0.708 and p=0.720); constriction velocity (p=0.646 and 0.347); nor dilation velocity (p=0.716 and 0.194) for the right and left eye groups respectively. Paired t-test found no difference in NPi (p=0.146). Among those with unilateral cataract (n=59). Conclusions:  The presence of cataract does not alter the PLR findings assessed with a pupillometer.